The impact of Islam on the sultanate of Melaka’s legal system during the 15th century - Mamat, Ismail (Malaysian Historical Society, 2018)
Malacca was one of the major centres of Islam the Malay Archipelago before the coming of the 20th century. It has played a significant role in Malay history in general and in the history of modern Malaysia in particular. The Sultanate of Malacca is a glorious page in Malay history and one of the most prosperous kingdoms in the Malay world. The importance of the Malay Sultanate of Malacca has been well-documented and much has been written about it by many authors either by Malaysians or non-Malaysians. My aim is to present the Islamization of Malacca and its impact on this Malay historical state, as well as its role in the formation of the Malay-Islamic civilization. The history of the Islamization of the Malay Archipelago in general is still considered a much-neglected field, particularly the period from the thirteenth to the sixteenth century. The very concept of Islamization has not even been understood by historians of the Malay world. This article attempts to look at the impact of Islam on the legal system of the Sultanate during the 15th century. It is hope that this article will shed some lights on the significant role played Islam in Malacca by looking at how Malacca, with the advent of Islam, developed into the strongest and most influential centre of Islam in the 15th century. Malacca grew from an unknown place during the pre-Islamic period to become one of the well-known centres of Islamic religion and culture in the region. Islam has changed the status of Malacca after reducing its pre-Islamic customs and ways of life.